O ‘ocaso’ do curso de formação de professores em Ciências Biológicas : constructos multidimensionais do ‘crepúsculo’ acadêmico - Silva, Nadja Fonsêca da (2017)
This research aims to understand and analyze – critical and reflexively — the reasons and motivation of teachers and students who took the metaphorical ‘sunset’ - that is defined in astronomy as the moment when the trailing edge of the Sun's disk disappears below the horizon - of the Biological Sciences course from UNICEUMA University in Maranhao State; identify and clarify the representations of the ' sunset ' of biological sciences such as understanding in methodological terms by teachers and students of the last edition of this course; clarify visions, concepts, beliefs, aspirations, perceptions, feelings and knowledge that may be significant to express views of students and teachers in the theaching course, as well as in professional practice teaching in biological sciences. The thesis contained in this process is concerned the ' sunset ' of the Biological Sciences course which can be resized for the dawn of a new/other course from the effective involvement of their specific social body - teachers, students and administrators – at the University in a new proposal, precisely for the quality of its actions and reactions. For the methodological terms of development of this work individual interviews were held with six education teachers which were recorded, transcribed and the episodes cut – transformed into data — from the discursive, textual analysis of questionnaires with the twelve graduating students of the Biological Sciences, aiming to analyze the verbal interactions that reveal the senses and meanings of ' sunset ' in this profissional course in biological sciences research institution. With the research guidelines the interaction voices of subject teachers and students from the research approach to narrative, thematic axes were established, which array the training of teachers and community of practice in order to study the movement of self-organizing processes such as: independent learning, self-knowledge; self-efficacy, self-regulation; selfsystem; authorship/autonomy through reflections and actions, expanded the senses and meanings of the social body of the University which includes faculty/students/managers. From the analysis and critical reflection on the possibility of overcoming the ' sunset ' in the course of biological sciences makes it possible to understand that from what it was called academic resilience teachers, students and administrators can afford to propose a new course of biological sciences efficiently and effectively for teacher education in this area.